THE INFLUENCE OF WORK-LIFE BALANCE ON EMPLOYEE JOB SATISFACTION AT BANGLI CLASS IIA NARCOTICS CORRECTIONAL INSTITUTION - Abhiwikrama, Sang Agus Kurnia; Wibowo, Padmono (Universitas Nusa Cendana, 2025)
This research aims to analyze the influence of work-life balance on employee job satisfaction at the Lapas Narkotika Kelas IIA Bangli. Work-life balance is an important factor that can influence the level of job satisfaction, especially in the context of a work environment that has high demands and pressure. This research uses quantitative research methods with techniques of non-probability sampling with as many as 84 employees. The data collection technique was carried out using a questionnaire distributed via Google Form. There are 20 statements used as indicators in this research. The data analysis technique used was through normality tests, significance tests, and determination tests, which were processed using IBM SPSS version 27 software. The results showed that there is an influence of work-life balance on employee job satisfaction. The determination test results indicate that the work-life balance has an influence of 57.3% on the job satisfaction variable, while the remaining 42.7% is influenced by other variables not explained in this research. Keywords : Work Life Balance; Job Satisfaction; Employees; Correctional Institutions